Pengembangan Skala Kualitas Kehidupan Kerja Pada Karyawan Muslim Di UKM - Dwi Despiana; Arief Fahmie; Elisa Kusrini (LPPM Universitas Abdurrab, 2025)
This study aims to design and validate the quality of work life (QWL) measurement instrument for use in Small and Medium Enterprises (SMEs) setting, involving 196 Muslim participants. Using the Exploratory Factor Analysis (EFA) method, the Kaiser-Meyer-Olkin (KMO) value was found to be 0.766, while Bartlett’s Test of Sphericity yielded a value of 1.872 with a significance level of 0.000 (p < 0.05). The analysis identified four primary factors: compensation and interpersonal relations, job satisfaction, support facilities and career development, and organizational climate, comprising a total of 26 items. The reliability test using Cronbach’s Alpha produced a coefficient of 0.882, indicating high internal consistency. Concurrent validity testing showed a significant positive correlation between the FED-QWLS and the QWLS, with a correlation coefficient of r = 0.846 and p = 0.000 (p < 0.01). In contrast, the correlations between both the FED-QWLS and QWLS with the SDS were r = -0.052 (p = 0.614) and r = -0.159 (p = 0.122), respectively, indicating no significant negative relationship between the QWL instruments and the SDS. The strength of this study focuses on employees in the MSME sector, as well as the efficiency of the developed instrument, which includes only 26 items, making it user-friendly and time-efficient for respondents.